Analysis of Patent Activity in R.E. Kavetsky Institute of Experimental Pathology, Oncology and Radiobiology of the NAS of Ukraine - Pyatchanina, T.V.; Ogorodnik, A.M.; Vasilyev, O.V.; Mazur, M.G. (Science and Innovation, 2024)
Introduction. The effectiveness of innovation activities of R&D oncology institutions is determined by the level of legal protection of intellectual property and affects the degree of implementation of research results in health care practice. Problem Statement. Combatting cancer is one of the most important medical and social problems of our time and progress in solving it can be achieved through the use of fundamental knowledge as a significant source of innovation. Purpose. To assess the status of patent and inventory activities of the RE Kavetsky Institute of Experimental Pathology, Oncology and Radiobiology of the National Academy of Sciences of Ukraine (IEPOR) in terms of the formation of strategic management decisions concerning its optimization.Materials and Methods. The main quantitative indicators of patent and invention activities of the IEPOR for 2009-2017, in particular, the number of applications and the number of patents issued; the index of patents of various types (for inventions, utility models, industrial designs) obtained; and rating of patent activities by the IEPOR departments have been evaluated. On the basis of the quantitative analysis and analysis of the international patent classification (IPC) of IPR objects, the orientation of the IPR objects by themes and subjects has been studied. Results. The peaks of patent activities were reported for 2010 (13 objects of IPR), 2013 (17 objects of IPR), and 2016 (12 objects of IPR). Data analysis for 2009-2017 on the received patent documents of various types has shown the priority of declarative patents for utility model. The patenting rating for 2009-2017 by the IEPOR research departments shows a different level of patent activities of researchers. A characteristic feature of the development of patent and inventory activities of researchers is the thematic orientation of the objects of IPs in full accordance with the main directions of the research work of the institute. Conclusions. The indicators of patent activities show a high level of the scholarly research activities and innovative potential of the institute and are an informative basis for the formation of strategic management decisions regarding the optimization of patent and invention activities.